2019
DOI: 10.1155/2019/4090549
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin C on the Prevention of Ischemia-Reperfusion Brain Injury: Experimental Study in Rats

Abstract: Background. Reperfusion syndrome after carotid endarterectomy is a complication associated with cerebrovascular self-regulation in a chronically hypoperfused cerebral hemisphere, leading to severe neurological damage. Vitamin C is an important antioxidant in brain metabolism that has shown some neuroprotective actions. Objective. To investigate the potential effects of vitamin C on cerebral reperfusion in comparison with placebo (saline) in rats. Methods. Male Wistar rats were divided into 3 groups: (i) Sham (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Studies by Das Gupta et al [28,29] reported that alcohol consumption is a risk factor for OA, so in daily life, it is recommended to drink less alcohol and eat more fresh vegetables, fruits, and soy products. Studies by McAlindon et al [30,31] reported that prolonged sunlight exposure is a protective factor for OA, because vitamin D has the activity of regulating bone metabolism in the body, it is mainly synthesized in the skin through sunlight, and prolonged sun exposure results in high levels of active vitamin D synthesized in the body, and active vitamin D can promote bone growth and metabolism, which protects the body from OA. e results of this study suggest that body mass index increases the risk of OA.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Das Gupta et al [28,29] reported that alcohol consumption is a risk factor for OA, so in daily life, it is recommended to drink less alcohol and eat more fresh vegetables, fruits, and soy products. Studies by McAlindon et al [30,31] reported that prolonged sunlight exposure is a protective factor for OA, because vitamin D has the activity of regulating bone metabolism in the body, it is mainly synthesized in the skin through sunlight, and prolonged sun exposure results in high levels of active vitamin D synthesized in the body, and active vitamin D can promote bone growth and metabolism, which protects the body from OA. e results of this study suggest that body mass index increases the risk of OA.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were randomly divided into the following groups ( n = 10): Firocoxib (10 mg/kg), vitamin C (750 mg/kg) alone, or firocoxib (10 mg/kg) in combination with vitamin C (750 mg/kg), administered intraperitoneally 30 min before I/R induction [ 19 , 20 , 21 , 22 ]. Animals were anesthetized with sodium pentobarbital (45 mg/kg) and the induction of I/R was performed as previously described [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hence, there remains an unmet need to identify potential therapeutic agents that can address the intricate pathophysiology of ischemia/reperfusion retinal injury. Notably, antioxidants, including vitamins C and E, have shown promising therapeutic benefits in retinal ischemic injury and rodent stroke models [ 9 , 10 , 11 ]. Additionally, free radical scavengers, like NXY-059 (disodium 2,4-sulphophenyl- N -tert-butylnitrone, Cerovive) and thiol-containing N -acetyl cysteine, have proven effective in reducing the infarct size and improving neurological outcomes in brain stroke models [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%